Operator readiness towards adventure tourism safety procedure during covid – 19. A case study of rafting activities in Gopeng, Perak - Miskam, Mohd. Rezal (2022)
Safety procedure is very important in doing tourism activity especially when it involved adventure setting. Nowadays, with the cases of COVID – 19 still arising, the concern over safety is high. People are keen to travel after a long restriction because of the pandemic. It is a responsibility to the tourism operator to fulfilled their wants and delivery excellent service quality without compromising safety aspect trough out the whole process. Is tourism operator ready in term of safety procedure in their place? Therefore, this is in line with the aim of this research which to analysed operator readiness towards adventure safety procedure during COVID -19. Rafting can be considered as hard adventure tourism activities in natural setting. It required mental and physical strength. Three objectives have been out lined for this research. First, to identified the factor of safety procedure for adventure activities that has been affected the rafting activities during COVID -19. Second, to examine the factors of rafting operator readiness towards safety procedure during COVID-19. Third, to understand the challenges of adventure tourism operator in providing safety procedure during COVID -19. Qualitative approach was chosen for these research. Data was gathered through researcher observation and interview. Five rafting operators were interviewed using in- depth semi structure question. Data collection then was analyzed using thematic analysis. The finding shows that rafting operator in Gopeng, Perak are ready to serve the tourist . They have prepared what it takes to deliver safe experience to their tourist.